2019
DOI: 10.3390/w11040774
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Detection of the E. coli Bacteria in Drinking Water Treatment Plants through an E-Nose and a Volatiles Extraction System (VES)

Abstract: Water quality control remains an important topic of public health since some diseases, such as diarrhea, hepatitis, and cholera, are caused by its consumption. The microbiological quality of drinking water relies mainly on monitoring of Escherichia coli, a bacteria indicator which serves as an early sentinel of potential health hazards for the population. In this study, an electronic nose coupled to a volatile extraction system (was evaluated for the detection of the emitted compounds by E. coli in water sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Detection of E. coli should lead to further action, like additional sampling and investigation of potential sources such as inadequate treatment or breaches in distribution system integrity. E. coli should be checked in any water to ascertain quality since it is a bacteria indicator which works as an early sentinel of possible health hazards for the community [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Detection of E. coli should lead to further action, like additional sampling and investigation of potential sources such as inadequate treatment or breaches in distribution system integrity. E. coli should be checked in any water to ascertain quality since it is a bacteria indicator which works as an early sentinel of possible health hazards for the community [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The survey of matrix effects validated the selectivity of the procedure for E. coli due to the competition of foreign interferences for available adsorption and desorption by nanocomposite. Importantly extraction and desorption via SPE method usually increase the selectivity of analyte removal [15,16,20]. Here, the removal of typical gram-positive bacterium (Bacillus subtilis) as an interference model organism (uptake and extraction of 10 7 CFU ml − 1 Bacillus subtilis with 0.003 g nanocomposite in 2 ml methanol) was investigated and the results showed that in the case of the gram-positive bacteria removal e ciency was very low compared to E. coli.…”
Section: Effect Of Contact Timementioning
confidence: 99%
“…A set of TGS, MiSC, and SHT75 sensors are used along with a bio-inspired neural network algorithm. In [15], samples are taken from the Pamplona and Toledo DWTPs in the northern Santander region (Colombia) to evaluate a multisensory system. The tests were executed utilising PCA, deterministic finite automaton (DFA), a probabilistic neural network (PNN), and TGS sensors.…”
Section: Literature Studymentioning
confidence: 99%